Rock falls in the Mont Blanc Massif in 2007 and 2008 - Ravanel, L. (Ludovic); Allignol, F. (Françoise); Deline, P. (Philip); Gruber, S. (Stephan); Ravello, M. (Mario) (Landslides, 2010)
Due to a lack of systematic observations, the intensity and volume of rock falls and rock avalanches in high mountain areas are still poorly known. Nevertheless, these phenomena could have burly consequences. To document present rock falls, a network of observers (guides, mountaineers, and hut wardens) was initiated in the Mont Blanc Massif in 2005 and became fully operational in 2007. This article presents data on the 66 rock falls (100 m3 ≤ V ≤ 50,000 m3) documented in 2007 (n = 41) and 2008 (n = 25). Most of